Inequalities in time to diagnosis of Down Syndrome in Bolivia - Daniel Linares Terrazas; Beatriz Luna Barrón; Gonzalo Taboada López (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2024)
Down Syndrome is the most common genetic condition and a leading cause of intellectual disability. Individuals in rural areas, particularly those with disabilities, often face disparities in healthcare access. Analyzing clinical records of patients diagnosed with Down Syndrome between 2013 and 2022 by the Institute of Genetics at the Universidad Mayor de San Andrés in La Paz, Bolivia, this study examined the time to diagnosis for 250 patients with Down Syndrome. The findings revealed that patients from rural areas with Down Syndrome take an average of five months to receive a diagnosis, compared to two months in urban areas (p<0.001). No significant differences were found in the time to diagnosis based on gender. However, a higher proportion of males from rural areas was observed (p=0.03). The results suggest that individuals in rural areas face challenges in receiving a timely diagnosis. On the other hand, women may not be brought to cities for proper diagnosis and treatment due to gender biases in certain communities. The importance of improving access to early diagnosis and treatment in rural areas is emphasized.